1992
DOI: 10.1203/00006450-199206000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal Protein-Calorie Malnutrition on the Phospholipid Composition of Surfactant Isolated from Fetal and Neonatal Rat Lungs. Compensation by Inositol and Lipid Supplementation

Abstract: ABSTRACT. The effects of a maternal protein-calorie malnutrition during gestation and lactation were analyzed on fetal and postnatal lung growth and maturation, including a surfactant fraction isolated from lung tissue. There was a considerable reduction in body weight and in wet and dry lung weights of malnourished pups. Lung protein and DNA concentrations were similar in both groups except in late gestation (lung hyperplasia) and 2 and 1 5 d after delivery (hypocellularity). Lung glycogen breakdown was slowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 16 publications
(29 reference statements)
1
9
0
1
Order By: Relevance
“…Guarner et al reported that phosphatidyl choline, a surfactant lipid component, is decreased in the fetal lungs derived from malnourished pregnant rats (15). The present study showed that the levels of SP-A in the fetal lungs and the amniotic fluid from protein-malnourished pregnant rats were significantly lower than those from preg nant rats receiving a normal protein diet.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Guarner et al reported that phosphatidyl choline, a surfactant lipid component, is decreased in the fetal lungs derived from malnourished pregnant rats (15). The present study showed that the levels of SP-A in the fetal lungs and the amniotic fluid from protein-malnourished pregnant rats were significantly lower than those from preg nant rats receiving a normal protein diet.…”
Section: Discussionsupporting
confidence: 45%
“…However, there are few or no reports regarding the effects of nutritional states of pregnant mothers on surfactant protein levels in the fetal lungs. Malnutrition during pregnancy causes a delay in fetal lung maturation, and decreased respiratory functions in newborn infants (15,16). The purpose of the present study was to investigate the effects of protein malnutrition on the levels of SP-A in the fetal lungs and the amniotic fluid in pregnant rats.…”
mentioning
confidence: 97%
“…Malnutrition can delay somatic growth and the development of new alveoli in addition to decreasing muscle strength, thereby prolonging the need for mechanical ventilation. In animal models, early malnutrition has been shown to alter surfactant lipid composition [11] .…”
mentioning
confidence: 99%
“…1999; 75(4):267-270: malnutrition, nicotine, lung phospholipids. descritos [1][2][3][4][5][6] , assim como também o impacto da desnutrição da rata grávida sobre seu feto [7][8][9][10] .…”
Section: Introductionunclassified